Defragmenting resource management on the Southeast Arm of Lake Malawi: Case of Fisheries - Maxon Ngochera; Steve Donda; Mafaniso Hara; Erling Berge (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
The Southeast Arm of Lake Malawi catchment has a wide range of natural resources that require prudent management for sustainability and maximisation of benefits. The current management practice is government sector based, with individual Departments and Ministries using their own policies, legislations and management approaches, yet dealing with the same composite resource and user communities. This has resulted in fragmentation of management leading to the lack of alignment between formal and informal institutions, and competition for power and authority for management. Fragmentation is also leading to loss of resource rent. This paper analyses how and why management is fragmented in the Southeast Arm of Lake Malawi catchment and suggests how management could be defragmented, with special interest on fisheries. Activities with high negative impacts on fisheries include: overfishing; soil erosion resulting in siltation and turbidity of the lake; chemical and organic pollution; loss of access to land and beaches; and habitat loss. There is need for a better and more holistic understanding of how human activities represent both livelihood benefits and a threat to sustainability of natural resources in order to find ways for balancing these two aspects. We suggest that to increase the efficacy of management of Lake Malawi's Southeast Arm will require 'defragmented decentralization', an approach whereby devolution of authority and responsibility are ceded to the district and local levels, respectively.
Keywords: H11; H70; P48; Q28; 330; Management; institutions; fragmentation; defragmented decentralisation; devolution; Lake Malawi